PERENCANAAN PENDIDIKAN BERBASIS FITRAH DI SEKOLAH ALAM SE-PROVINSI LAMPUNG - Paulina, Tila; Pahrudin, Agus; Syafrimen, Syafrimen; Koderi, Koderi (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2024)
Nature-based education planning in natural schools in Lampung Province has given rise to a new approach in integrating natural values, natural elements and local wisdom in the curriculum. This research is motivated by the complexity of educational needs and the call of the times that demand changes in the concept of education. This research uses a qualitative approach with case studies as the main method. The case study method provides an in-depth description of the implementation of the planning strategy, while qualitative analysis is used to gain an in-depth understanding of its impact. The research results show that developing a nature-based curriculum involves an in-depth process in designing a special curriculum that reflects natural values, integrates natural elements, and involves education experts and community leaders. Training for educators through regular workshops and mentoring by fitrah experts has a positive impact on increasing understanding of the concept of fitrah and the quality of learning. The integration of local values creates a learning environment rich in Lampung cultural wisdom. Facilities and learning environments that support direct interaction with nature create learning spaces that allow students to be actively involved. Parental and community participation is realized through routine programs and partnership forums, strengthening their involvement in shaping children's character. Holistic periodic evaluation involving all stakeholders creates the basis for comprehensive monitoring of student development. Collaboration with local governments and educational institutions opens up opportunities for financial support and exchange of experiences, strengthening the concept of natural schools based on nature. Despite facing limited resources and potential resistance, this research shows that nature-based educational planning in natural schools in Lampung Province has great potential to create a responsive and holistic educational environment.